'Human bocavirus in Pakistani children with gastroenteritis'. Issue 4 (21st January 2015) - Alam, Muhammad Masroor; Khurshid, Adnan; Shaukat, Shahzad; Sharif, Salmaan; Suleman, Rana Muhammad; Angez, Mehar; Nisar, Nadia; Aamir, Uzma Bashir; Naeem, Muhammad; Zaidi, Syed Sohail Zahoor
<x xml:space="preserve">Abstract</x> Human Bocaviruses (HBoV) have been detected in human respiratory and gastrointestinal infections worldwide. Four genotypes of HBoV (HBoV1–4) have been described; HBoV‐1 is associated with respiratory tract infections while HBoV‐2, ‐3, and ‐4 genotypes are considered as entero‐pathogenic although the exact role largely remains unclear. The global prevalence of HBoV has been reported, but the epidemiological data from Pakistan is largely unavailable to date. This study was conducted to understand the genetic diversity and disease prevalence of HBoV in hospitalized Pakistani children with acute diarrhea. During 2009, a total of 365 stool samples were collected from children hospitalized with gastrointestinal symptoms (as per WHO case definitions) at Rawalpindi General Hospital, Pakistan. Demographic and clinical data were recorded using a standardized questionnaire. The samples were tested for HBoV and rotavirus using real‐time RT‐PCR and ELISA, respectively. There were 47 (13%) samples positive for HBoV with 98% (n = 46) showing co‐infection with rotavirus. HBoV‐1 was the most frequently detected and was found in 94% samples followed by HBoV‐2 and HBoV‐3 genotypes. The mean age of infected children was 7.57 ± 5.4 months while detection was more frequent in males (n = 32, 68%). All cases recovered after 2.43 ± 1.0 mean days of treatment. On phylogenetic analysis, HBoV strains from Pakistan clustered closely with viruses from neighboring Bangladesh and China. These findings represent the first known epidemiological study in Pakistan to investigate the role of HBoV in acute gastroenteritis. The clinical data demonstrates that HBoV is not significantly associated with gastroenteritis alone and predominantly co‐infections with rotavirus are found. J. Med. Virol. 87:656–663, 2015. © 2015 Wiley Periodicals, Inc.